HUBUNGAN KELELAHAN DENGAN TINGKAT DEPRESI POSTPARTUM PADA IBU NIFAS - Natasya Putri Suryadi; Putri Yuliantie; Siti Noor Hasanah; Novalia Widiya Ningrum (Jurnal Kesehatan, 2025)
Postpartum depression is a psychological condition often experienced by mothers after childbirth, characterized by feelings of sadness, anxiety, and fatigue. This condition is closely related to physical and mental exhaustion during the postpartum period. To determine the relationship between fatigue and the level of postpartum depression in postnatal mothers at the Pekauman Health Center, Banjarmasin. This study used a quantitative descriptive design with a cross-sectional approach. The population included 56 postpartum mothers, and 30 were selected using quota sampling. Data were collected using the Postpartum Fatigue Scale (PFS) and the Edinburgh Postnatal Depression Scale (EPDS), then analyzed using the Chi-Square test. Most respondents were 20–35 years old (87.9%), unemployed (63.6%), had secondary education (50.0%), and were multiparous (63.3%). The majority experienced moderate fatigue (63.3%) and were at risk for postpartum depression (63.6%). Chi-Square test results showed a significant relationship between fatigue and postpartum depression levels (p = 0.000 < 0.05). There is a significant relationship between the level of fatigue and postpartum depression. The higher the level of maternal fatigue, the greater the likelihood of postpartum depression. Abstrak: Depresi postpartum merupakan kondisi psikologis yang sering dialami oleh ibu setelah melahirkan, ditandai dengan perasaan sedih, cemas, dan kelelahan. Kondisi ini erat kaitannya dengan kelelahan fisik dan mental selama masa nifas. Mengetahui hubungan antara kelelahan dengan tingkat depresi postpartum pada ibu nifas di wilayah kerja Puskesmas Pekauman Banjarmasin. Penelitian ini menggunakan desain deskriptif kuantitatif dengan pendekatan cross-sectional. Populasi berjumlah 56 ibu nifas, dengan sampel 30 responden yang diambil menggunakan teknik quota sampling. Instrumen penelitian meliputi kuesioner Postpartum Fatigue Scale (PFS) dan Edinburgh Postnatal Depression Scale (EPDS). Analisis data menggunakan uji Chi-Square. Sebagian besar responden berusia 20–35 tahun (87,9%), tidak bekerja (63,6%), berpendidikan SMA (50,0%), dan multipara (63,3%). Mayoritas ibu mengalami kelelahan sedang (63,3%) serta berisiko depresi postpartum (63,6%). Uji Chi-Square menunjukkan adanya hubungan signifikan antara kelelahan dan depresi postpartum (p = 0,000 < 0,05). Terdapat hubungan bermakna antara tingkat kelelahan dengan tingkat depresi postpartum. Semakin tinggi tingkat kelelahan, semakin besar risiko mengalami depresi postpartum.